1998
DOI: 10.1021/np970364d
|View full text |Cite
|
Sign up to set email alerts
|

New Triterpenes from Machaerocereus eruca

Abstract: Four triterpenes, three lupanes, and a germanicane were isolated from Machaerocereus eruca. The germanicane derivative (1) was determined to be 3β,19α-dihydroxygermanican-28-oic acid and named machaeroceric acid. The three new lupane derivatives were identified as 21-ketobetulinic acid (2), 16β-hydroxybetulinic acid (3), and 22β-hydroxystellatogenin (4), respectively, on the basis of their spectroscopic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Compound 13 was obtained as a white amorphous powder, with the molecular formula C 36 (Table 4) 23 showed that they had the same olean-18-ene skeleton. The signals of C-3 and C-28 were observed at d C 89.3 and 175.8, respectively, which implied that compound 15 must be a bisdesmosidic triterpene saponin.…”
Section: Structure Elucidation Of New Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compound 13 was obtained as a white amorphous powder, with the molecular formula C 36 (Table 4) 23 showed that they had the same olean-18-ene skeleton. The signals of C-3 and C-28 were observed at d C 89.3 and 175.8, respectively, which implied that compound 15 must be a bisdesmosidic triterpene saponin.…”
Section: Structure Elucidation Of New Compoundsmentioning
confidence: 99%
“…18 As part of an ongoing search for bioactive natural products from traditional folk medicine, the aerial parts of E. prostrata were investigated. Twentyfour compounds, including eight mono-, di-, and trithiophene derivatives (1-7), two polyacetylenic glucosides (8 and 9), and fifteen mono-, sesqui-, and triterpenoid glycosides (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), were isolated from E. prostrata. Herein, we report the isolation and structural elucidation of one new bithiophenes (2), two new polyacetylenic glucosides (8 and 9), and six new terpenoid glycosides (10)(11)(12)(13)(14)(15) from E. prostrata.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allobetulin (3β hydroxy 19β,28 epoxy 18α ole ane) (I) and its derivatives belong to the group of trit erpenoids of the germanican family, a very rare class of natural compounds [1,2]. Allobetulin and related compounds (e. g., 28 oxoallobetulon [3] and 3β ace toxy 18α oleanan 28,19β lactam [4]) can be synthe sized from widely occurring natural lupane triterpe noids (e.g., betulin) using the Wagner-Meerwein rearrangement in the presence of acids [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…These are allobetulin derivatives: 3β О cinnamate (XI), 1 oxo 2 ene (XII), 5β methyl 25 nor 9 ene (XIII), (3R,5R) and (3S,5S) 1,2,4 trioxolanes (XIV) and (XV), 3α,5α epoxide (XVI), [3,2 d] [1,2,3]thiadiazole (XVII), 3 oxime (XVIII), and 3 semicarbazone (XIX).…”
Section: Introductionmentioning
confidence: 99%